Reproduksi kultural dan habituasi pada masyarakat pendatang Kampung Miliarder Desa Tlobo, Kecamatan Jatiyoso, Kabupaten Karanganyar - Wibowo, B.Mayang Sada; Naredia, Shubuha Pilar (Universitas Negeri Malang, 2024)
This paper aims to describe the cultural reproduction and habituation of immigrant community of the Kampung Miliarder using Bourdieu's cultural reproduction practice scheme. Data collection techniques use observation, in-depth interviews, and documentation. Data analysis techniques using interactive models. Data validity to ensure data validity. The results showed the practice of cultural reproduction that occurred in the immigrant community of Kampung Miliarder. To these actors are attached habitus accumulated with various capitals consisting of cultural capital, social capital, economic capital, symbolic capital. The practice of cultural reproduction results from the struggle that actors engage in with the accumulation of habitus and capital. The forms of cultural reproduction found in this study are; the process of buying and selling, symbolic violence, and gratitude. In the Kampung Miliarder of Tlobo Village, habituation is divided into; socio-cultural and socio-economic. Artikel ini bertujuan untuk menggambarkan reproduksi kultural dan habituasi masyarakat pendatang Kampung Miliarder menggunakan skema praktik reproduksi kultural milik Bourdieu. Teknik pengumpulan data menggunakan observasi, wawancara mendalam, dan dokumentasi. Tenik analisis data menggunakan model interaktif. Validitas data guna menjamin kebsahan data. Hasil penelitian menunjukan praktik reproduksi kultural yang terjadi pada masyarakat pendatang Kampung Miliarder. Pada aktor tersebut melekat habitus yang diakumulasikan dengan berbagai modal yang terdiri atas modal budaya, modal sosial, modal ekonomi, modal simbolik. Praktik reproduksi kultural diakibatkan oleh perjuangan yang dilakukan aktor dengan akumulasi habitus dan modal. Bentuk reproduksi kultural yang ditemukan dalam penelitian ini berupa; proses jual beli, kekerasan simbolik, dan syukuran. Pada Kampung Miliarder Desa Tlobo, habituasi terbagi menjadi; sosio-kultural dan sosio-ekonomi.